Linked Open Data in Smart Cities: An application in the domains of Mobility and Education - Belizario, Mateus G.; Berardi, Rita Cristina G. (Anais da Escola Regional de Banco de Dados (ERBD); 2022: Anais da XVII Escola Regional de Banco de DadosDO - 10.5753/erbd.2022.223537, 2022)
The fast transition to a highly urbanized population means that governments face new challenges in managing data and information in urban spaces. One of them concerns the need for information models of similar semantics and the ability to share and connect information from different sources and in heterogeneous formats, allowing the improvement of operational decision making by managers and citizens. In this sense, the objective of this work is to carry out a proof of concept integrating open data from the domains of education and mobility, using ontologies. The data used are from the city of Curitiba relating the academic performance of students at different levels and the characteristics of urban mobility in the city. The linked data obtained is an indication of the relationship between the academic performance of students in the municipality and the characteristics of urban mobility in the city.